Antihypertensive Effect of Sodium-Glucose Cotransporter 2 Inhibitors and Glucagon-like Peptide 1 Receptor Agonists - Marijana Tadic; Cesare Cuspidi (Cardiology Discovery)
An increasing body of evidence shows that new antidiabetic drugs—particularly sodium-glucose cotransporter 2 (SGLT2) inhibitors and glucagon-like peptide 1 (GLP-1) receptor agonists—have a beneficial effect on cardiovascular outcome. The majority of these studies have been performed in patients with heart failure and the results have shown first positive effect on blood pressure (BP) reduction. These effects are more pronounced with SGLT2 inhibitors than with GLP-1 receptor agonists. However, the reasons and mechanisms of action inducing BP reduction are still not sufficiently clear. Proposed mechanisms of SGLT2 inhibitors involve the natriuretic effect, modification of the renin-angiotensin-aldosterone system, and/or the reduction in the sympathetic nervous system. GLP-1 receptor agonists have several mechanisms that are related to glycemic, weight, and BP control. Current data show that SGLT2 inhibitors have a stronger antihypertensive effect than GLP-1 receptor agonists, which is mainly related to their renal effect. Briefly, SGLT2 inhibitors increase the response to diuretics and decrease the meal-related antinatriuretic pressure by lowering post-prandial hyperglycemia and hyperinsulinemia and prevent proximal sodium reabsorption. SGLT2 inhibitors can be used as second-line therapy in patients with diabetes mellitus or heart disease and concomitant hypertension. This article aims to summarize current knowledge regarding the antihypertensive effect of SGLT2 inhibitors and GLP-1 receptor agonists.